IFCC Working Group Recommendations for Assessing Commutability Part 3: Using the Calibration Effectiveness of a Reference Material. (1st March 2018) - Budd, Jeffrey R; Weykamp, Cas; Rej, Robert; MacKenzie, Finlay; Ceriotti, Ferruccio; Greenberg, Neil; Camara, Johanna E; Schimmel, Heinz; Vesper, Hubert W; Keller, Thomas; Delatour, Vincent; Panteghini, Mauro; et al.
Abstract: A process is described to assess the commutability of a reference material (RM) intended for use as a calibrator based on its ability to fulfill its intended use in a calibration traceability scheme to produce equivalent clinical sample (CS) results among different measurement procedures (MPs) for the same measurand. Three sources of systematic error are elucidated in the context of creating the calibration model for translating MP signals to measurand amounts: calibration fit, calibrator level trueness, and commutability. An example set of 40 CS results from 7 MPs is used to illustrate estimation of bias and variability for each MP. The candidate RM is then used to recalibrate each MP, and its effectiveness in reducing the systematic error among the MPs within an acceptable level of equivalence based on medical requirements confirms its commutability for those MPs. The RM is declared noncommutable for MPs for which, after recalibration, the CS results do not agree with those from other MPs. When a lack of agreement is found, other potential causes, including lack of calibration fit, should be investigated before concluding the RM is noncommutable. The RM is considered fit for purpose for those MPs where commutability is demonstrated.